Data supporting: 'In-process nip point temperature estimation in automated tape placement based on analytical solution and remote thermal measurements' - Danezis, Anastasios; Skordos, Alexandros A.; Williams, David (Cranfield University, 2022)
FE and 1D predictions comparison: nip point temperature estimates by the analytical scheme and FE model.Inverse solution data: tool surface temperatures before and after the addition of Gaussian noise, irradiance profile applied in FE model and its approximations using the inverse solution. Metallic and insulating tool material.Example application- power variation: contains the data of the virtual experiment generated by the FE model, and analytical scheme estimates for different scenarios.
Keywords: 'Process modelling'; 'Process monitoring'; 'Composite and Hybrid Materials'; 'Aerospace Materials'; 'Automated tape placement'